2020
DOI: 10.3390/ma13215006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonation on the Water Resistance of Steel Slag—Magnesium Oxysulfate (MOS) Cement Blends

Abstract: Magnesium oxysulfate (MOS) cement has the advantages of lightweightedness, high strength, and low thermal conductivity, but the utilization of MOS cement is limited due to low water resistance. This paper studied the influence of steel slag and CO2 treatment on the compressive strength and water resistance of MOS cement. The hydration products and microstructures were characterized by X-ray diffraction (XRD), thermogravimetric analysis–differential scanning calorimetry (TG–DSC), scanning electron spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…However, the high concentrations of CaO and MgO in SS compromise its stability [19]. Recent studies indicate that the stability of SS can be enhanced through carbonation [20]. Due to the high content of belite (C 2 S) and lime (CaO), SS demonstrates excellent carbonation reactivity, as illustrated in Equations ( 1) and (2) [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high concentrations of CaO and MgO in SS compromise its stability [19]. Recent studies indicate that the stability of SS can be enhanced through carbonation [20]. Due to the high content of belite (C 2 S) and lime (CaO), SS demonstrates excellent carbonation reactivity, as illustrated in Equations ( 1) and (2) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Kuenzel et al [27] studied hydromagnesite and found that it can react with MgO or Mg(OH) 2 to form a hydraulic basic magnesium carbonate and even a novel type of magnesium carbonate cement. Hu et al [20] investigated the impact of SS hydration and carbonation on the properties of MOS cement. By incorporating varying proportions of SS, the study explored the effects of different carbon dioxide pressures on the modified MOS cement, ultimately identifying the most effective carbonation parameters and the cement products with the highest compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Steel slag (SS) is a by-product of the steel industry, the mineral composition of which is mainly calcium silicate. In China, steel slag has become one of the most important sources of industrial waste, with less than 20 % of SS currently being utilised [18]. The waste steel slag occupies a large area of land and leads to many serious environmental problems, so the reuse of SS has also garnered increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…A utilização de escória de aço em substituição ao MgO no cimento MOS, também foi estudada por Hu et al (HU et al, 2020). Os autores estudaram a influência da utilização da escória de aço e a cura por carbonatação nas resistências à compressão e à água do cimento MOS.…”
Section: Cimentos De Oxissulfato De Magnésio (Mos)unclassified
“…O coeficiente de perda de resistência é utilizado para determinar a resistência à água das amostras, conforme (GOMES et al, 2021a;HAO;ZHAO, 2019;HU et al, 2020;ZHANG et al, 2020). Após a cura em ambiente controlado por 28 dias, 6 corpos de prova foram colocados em água a 20 ± 3°C, a resistência à compressão das amostras após 28 dias de imersão em água foi medida e utilizada para calcular o coeficiente de perda de resistência à compressão na água (Kcn) da amostra.…”
Section: Misturasunclassified